2000
DOI: 10.1093/jn/130.9.2200
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Intervention with Carotenoid-Rich Vegetable Products Reduces Lipid Peroxidation in Men

Abstract: Because of their antioxidant properties, carotenoids may have beneficial effects in preventing cancer and cardiovascular disease. However, in humans consuming carotenoid-rich vegetables, data concerning the antioxidant effects of carotenoids are rather scarce. A human intervention trial was conducted, therefore, to determine whether a moderately increased consumption of carotenoid-rich vegetables would influence the antioxidant status in 23 healthy men. This short-term feeding study lasted 8 wk during which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(97 citation statements)
references
References 49 publications
8
85
1
3
Order By: Relevance
“…Hininger et al (2001) further supplemented healthy male volunteers with 15 mg of natural tomato lycopene extracts for 12 weeks, and reported no effects on LDL oxidizability. In comparison with these studies showing null effects of tomato lycopene supplementation on lipoprotein oxidation, Bub et al (2000) reported a 18% increase in LDL lag time in 23 healthy men, following a 2-week tomato juice consumption providing a higher dose of lycopene (40 mg/day). It should also be noted that following a 2-week carotenoid depletion period, the plasma lycopene levels in these healthy volunteers were reduced to a concentration of 0.16 mmol/l of all-trans lycopene and 0.15 mmol/l of cis-lycopene.…”
Section: Mechanisms Of Action Of Lycopenementioning
confidence: 93%
“…Hininger et al (2001) further supplemented healthy male volunteers with 15 mg of natural tomato lycopene extracts for 12 weeks, and reported no effects on LDL oxidizability. In comparison with these studies showing null effects of tomato lycopene supplementation on lipoprotein oxidation, Bub et al (2000) reported a 18% increase in LDL lag time in 23 healthy men, following a 2-week tomato juice consumption providing a higher dose of lycopene (40 mg/day). It should also be noted that following a 2-week carotenoid depletion period, the plasma lycopene levels in these healthy volunteers were reduced to a concentration of 0.16 mmol/l of all-trans lycopene and 0.15 mmol/l of cis-lycopene.…”
Section: Mechanisms Of Action Of Lycopenementioning
confidence: 93%
“…However, the beneficial effects of this level of consumption have not been examined. Studies to date have concentrated on dietary enhancement of volunteers with carotenoid-rich vegetables (Hininger et al, 1997;van het Hof et al, 1999;Bub et al, 2000;Chopra et al, 2000) or provided subjects with a highly controlled diet with a very high fruit and vegetable component (9-10 servings per day) (Cao et al, 1998;Miller et al, 1998). Previous studies attempting to increase fruit and vegetable consumption in free-living volunteers demonstrated increases in plasma antioxidants (Zino et al, 1997), but no significant increase in plasma antioxidant capacity (Record et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The plant itself can protect the cell from oxidative damage by the non-enzymatic antioxidant system to eliminate excessive reactive oxygen species formed under adverse conditions [12]. When there are antioxidants for hydrogen production (such as phenols), the color of DPPH solution becomes shallow; ABTS •+ reacts with it and turn it into a colorless ABTS; And FRAP measures the antioxidant capacity of power by measuring the ability of Fe 3+ to be reduced to Fe 2+ [13]. The results showed that exogenous melatonin treatment increased the content of TPC, TFC, TFAC, AsA in leaves of kiwifruit seedlings, enhanced the antioxidant ability.…”
Section: Discussionmentioning
confidence: 99%